2012
DOI: 10.1590/s0102-311x2012000900016
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos acidentes escorpiônicos em Belo Horizonte, Minas Gerais, Brasil, 2005 a 2009

Abstract: Realizou-se um estudo epidemiológico observacional retrospectivo para caracterizar os acidentes escorpiônicos em Belo Horizonte, Minas Gerais, Brasil, entre 2005 e 2009. Foram coletados dados do Sistema Nacional de Informação de Agravos de Notificação (SINAN) e Sistema de Vigilância Epidemiológica (SISVE) e das fichas de atendimento do Hospital João XXIII. Observou-se um total de 2.769 casos no período (114,7/100 mil habitantes), tendência decrescente e maior ocorrência entre agosto e janeiro. A espécie Tityus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 3 publications
5
25
1
11
Order By: Relevance
“…A similar incidence in the number of males and females being stung by scorpions was observed in this study, which agrees with other reports 19,26,34,35 . These fi ndings are also in agreement with previous fi ndings describing the lower extremities as the sites most frequently stung in children 19,26,34,36 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A similar incidence in the number of males and females being stung by scorpions was observed in this study, which agrees with other reports 19,26,34,35 . These fi ndings are also in agreement with previous fi ndings describing the lower extremities as the sites most frequently stung in children 19,26,34,36 .…”
Section: Discussionsupporting
confidence: 93%
“…These fi ndings are also in agreement with previous fi ndings describing the lower extremities as the sites most frequently stung in children 19,26,34,36 . Many different reasons can account for why the children were stung, such as the highly activity level common in this age, activities close to or on the ground and walking barefoot 35 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was higher than the increase that has been estimated for all of Brazil: between 2001 and 2012, the accident rate went from 10.5/100,000 to 32.3/100,000. 4 The coefficient for Jequié also differs from what has been found in other municipalities in this country, such as in Campina Grande, state of Paraíba, from 2007 to 2012 7 and in Belo Horizonte, state of Minas Gerais, from 2005 to 2009, 8 where there were declines in the coefficient, from 132.0/100,000 to 108.0/100,000 and from 28.6/100,000 to 24.3/100,000, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Regarding the monthly distribution, it was observed that the accidents did not present seasonal behavior, and a certain degree 8 and in countries such as Iran 10 and Tunisia, 11 where scorpion accidents have been reported to be more frequent in the hotter and rainier periods of the year.…”
Section: Discussionmentioning
confidence: 99%